Cutin formation in tomato is controlled by a multipartite module of synergistic and antagonistic transcription factors - Yuan Shi; Changhao Deng; Xiangyin Lu; Yan Wang; Yaowen Pan; Deding Su; Wang Lu; Yuxiang Lin; Rui Li; Junnan Han; Yanwei Hao; Yi Chen; et al. (Cell Reports)
Summary: Cuticles protect plants from water loss and pathogen attack. We address here the functional significance of SlGRAS9, SlZHD17, and SlMBP3 in regulating cutin formation in tomato fruit. The study unveils the role of the multipartite “SlGRAS9-SlZHD17-SlMBP3-SlMIXTA-like” transcription factor module in cutin biosynthesis. Plants deficient in SlGRAS9, SlZHD17, or SlMBP3 exhibit thickened cuticles and a higher accumulation of cutin monomers, conferring extended fruit shelf life and higher tolerance to postharvest fungal infection. SlGRAS9 regulation of cutin is mediated by SlZHD17, a negative regulator of SlCYP86A69. SlZHD17 acts synergistically with SlMBP3 to repress SlCYP86A69, and its interaction with SlMIXTA-like prevents the binding to the SlCYP86A69 promoter, thereby releasing the repression of cutin biosynthesis. SlZHD17 and SlMBP3 synergistically repress cutin biosynthesis, while SlMIXTA-like and SlCD2 act antagonistically to SlZHD17 and SlMBP3 on this metabolic pathway. The study defines targets for breeding strategies aimed at improving cuticle-associated traits in tomato and potentially other crops.